Strategi Komunikasi Pemasaran Radio Maros FM dalam Meningkatkan Jumlah Pendengar - Hariana Anastasia; Sabaruddin Machmud (Journal of Communication Sciences (JCoS), 2020)
The purpose of this study was to determine: (1) Marketing Communication Strategy of Maros FM Radio in Increasing the Number of Listeners, (2) Factors influencing the marketing communication strategy of Maros FM Radio in increasing the number of listeners. The research method used is descriptive qualitative which aims to describe systematically and accurately about facts and characteristics about a particular population or field. Data collection methods used are, through the stages of observation, interviews and documentation. The results of this study indicate that: (1) Maros FM Radio Marketing Communication Strategy in Increasing the Number of Listeners consists of, Advertising, Sales Promotion, Public Relations & Publicity, Direct Marketing, Interactive Marketing, Word of Mouth, and Personal Selling. (2) While in terms of supporting factors, namely government-owned radio, the competition is still lacking, covering all segments, featured programs, the frequency is quite extensive. While the inhibiting factor is that broadcasters who are fluent in local languages are lacking, there are technical obstacles, the budget is determined by the government.